PENGARUH SUBSTITUSI TEPUNG AZOLLA (Azolla microphylla) DALAM RANSUM TERHADAP HEMOGLOBIN DAN HEMATOKRIT BROILER JANTAN - Muhammad Daffa Ewaldi; Farida Fathul; Madi Hartono; Siswanto Siswanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study aimed to determine the best percentage of Azolla microphylla flour substitution in broiler ration on hemoglobin and hematocrit of male broiler chicken. This study was conducted in March—April 2021 at Farm 1 cage 5 PT. Sinar Ternak Sejahtera, Wonodadi Village, South Lampung Regency. Blood samples were analyzed at the Lampung Veterinary Center Laboratory, Bandar Lampung City. This study used 24 male broilers with a completely randomized design (CRD) with four treatments, namely ration without Azolla microphylla flour substitution (P0), ration with 2,5% Azolla microphylla flour substitution (P1), ration with 5% Azolla microphylla flour substitution (P2), ration with 7,5% Azolla microhpylla flour substitution (P3) and each treatment was repeated three times. The data obtained were arranged in a simple tabulation and displayed in a histogram and then analyzed descriptively by comparing the hemoglobin and hematocrit values of this study with normal standards. The result showed that hemoglobin levels were P0 6,5±0,1 g/dl; P1 6,3±0,2 g/dl; P2 6,3±0,3 g/dl; dan P3 6,1±0,25 g/dl and treatments tends to reduce hemoglobin levels. The hematocrit values of the results of this study are 21,5±1,8%; P1 25,5±0,5%; P2 25,3±0,3%; dan P3 24,8±1,6%. The substitution of Azolla flour in the ration cannot maintain the hemoglobin levels at the normal standard, but can improve hematocrit values. Keywords: Azolla microphylla, hematocrit, hemoglobin, male broiler